PENERAPAN MODEL GI BERBANTUAN MEDIA VIDEO DENGAN PENDEKATAN KONTEKSTUAL DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Alfan Maulidiansyah Zen; Iis Aisyah; Kurniawan Kurniawan (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research is undermined by the problem that occurs in the SMAN 1 Tasikmalaya, which is the low ability of students to think creatively. The aim of this study is to find out the impact of the application of the learning model of group investigation assisted video media with a contextual approach in improving the creative thinking ability of students on economic subjects. The methods used are experimental methods with the type of experiment, with research design using non-equivalent control group design, as well as data collection techniques through double-choice tests. The results of the study showed that in the experimental class, the N-Gain score was 0.71, which means that there was a difference in student's creative thinking ability in economic subjects at the time before and after the application of the group investigation learning model with the help of video media with a contextual approach. Furthermore, there is a difference between students' creative thinking skills in experimental classes that use a group investigation learning model with a contextual approach to video media with a control class that uses a problem solving learning model. Thus, it can be concluded that the study study group learning model using video media with a context-oriented approach can improve students' creative thinking abilities.